The Social Control Model on the Risk of Adolescent Drugs Abuse - Purwandari, Eny; E. Prawitasari, Johana; Afiatin, Tina; Prihartanti, Nanik (International Journal of Psychosocial Rehabilitation, 2019)
The increasing national prevalence of drug abuse among adolescents in Indonesia highlight the need for an empirical model for effective social control. The aim of this study was to test the model originating from the social control theory, consisting of attachment, involvement, commitment, and belief. A sample of 241 high school students age between 15 – 17 years were selected using stratified sampling completed a cross sectional survey. Instrument used comprised of demographic information and measures of parental attachment, peer attachment, school commitment, and leisure time activity preference. Result of the Structural Equation Modell (SEM) showed that factors within the family, peer, and school settings significantly contributed towards the risk of drug abuse among adolescents. In the family setting, there is a difference between paternal and maternal attachment among at risk adolescents. Maternal attachment was found to be a stronger predictor in at risk adolescent. Therefore, preventive interventions on adolescents at risk of drug abuse should emphasize on developing strong bonding between mothers and child to control them from being influenced by external factors.